Framework for the optimization of online computable models. Issue 3 (29th April 2014) - Delinchant, Benoit; Wurtz, Frédéric; Vasconcelos, João; Coulomb, Jean-Louis
Abstract : Purpose: – The purpose of this paper is to make easily accessible models to test and compare the optimization algorithms we develop. Design/methodology/approach: – For this, the paper proposes an optimization framework based on software component, web service, and plugin to exploit these models in different environments. Findings: – The paper illustrates the discussion with optimizations in Matlab™ and R (www.r-project.org ) of a transformer described and exploitable from the internet. Originality/value: – The originality is to make easy implementation of simulation model and optimization algorithm coupling using software component, web service, and plugin.